2013
DOI: 10.1098/rsbl.2013.0317
|View full text |Cite
|
Sign up to set email alerts
|

To breed or not to breed: endocrine response to mercury contamination by an Arctic seabird

Abstract: Mercury, a ubiquitous toxic element, is known to alter expression of sex steroids and to impair reproduction across vertebrates but the mechanisms underlying these effects are not clearly identified. We examined whether contamination by mercury predicts the probability to skip reproduction in black-legged kittiwakes (Rissa tridactyla) from Svalbard. We also manipulated the endocrine system to investigate the mechanism underlying this relationship. During the pre-laying period, we injected exogenous GnRH (gonad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
154
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 170 publications
(162 citation statements)
references
References 15 publications
6
154
1
1
Order By: Relevance
“…Concerning the proximate mechanisms, Hg, in its methylated form, is known to disrupt reproductive hormones [1] such as the luteinizing hormone, a key pituitary hormone for the onset of breeding [3]. As found in two southern Catharacta skua species [10], Hg negatively impacted hatching probability of albatrosses, but only in individuals previously observed as breeders.…”
Section: (B) Survival and Contaminantsmentioning
confidence: 98%
“…Concerning the proximate mechanisms, Hg, in its methylated form, is known to disrupt reproductive hormones [1] such as the luteinizing hormone, a key pituitary hormone for the onset of breeding [3]. As found in two southern Catharacta skua species [10], Hg negatively impacted hatching probability of albatrosses, but only in individuals previously observed as breeders.…”
Section: (B) Survival and Contaminantsmentioning
confidence: 98%
“…In a recent study we have shown that moderate levels of mercury could be linked to non-breeding events in kittiwakes from Svalbard (Tartu et al 2013). In our study, however the decision to breed or not was unrelated to blood POP levels (neither to pesticides nor PCBs).…”
Section: Breeding Decision and Body-condition Indexmentioning
confidence: 99%
“…We studied kittiwakes in one plot of around 117 pairs breeding on cliff ledges at heights of 5-10 m. Female kittiwakes were sampled from 19 May to 7 June 2011, during the pre-laying period (i.e. copulations and nest building period), a key period for reproductive decisions during which females kittiwakes appear highly sensitive to stressors (Goutte et al 2010a(Goutte et al , 2011bTartu et al 2013). …”
Section: Study Area and Birdsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mercury (Hg) is an ubiquitous pollutant released to the environment from natural and anthropogenic sources Fitzgerald et al, 1998;Tartu et al, 2013;US Environmental Protection Agency, 2001). Hg bioaccumulates and bioamplifies within the food web (Watras et al, 1998), and poses a potential threat to fish, wildlife and human health (Hammerschmidt and Fitzgerald, 2006;Sandheinrich and Wiener, 2011).…”
Section: Introductionmentioning
confidence: 99%